Mewujudkan Sistem Hukum Nasional yang Adil dan Efektif: Urgensi Penataan Regulasi dalam Perspektif Politik Hukum di Indonesia - Wibowo, Ari; Dimyati, Asep Rohman; Junaedi, Junaedi (Indonesian Journal Publisher, 2025)
This study examines the urgency of regulatory reform in Indonesia from the perspective of legal politics to realize a national legal system that is just, effective, and responsive to societal needs. The shift toward a constitutional government has brought structural changes to Indonesia’s legal framework, particularly in expanding regulatory authority and complexity. Using a normative legal research method, the study applies statutory, theoretical, and conceptual approaches by analyzing primary to tertiary legal sources through qualitative analysis. The findings reveal that Indonesia’s regulatory framework has evolved through a long and fragmented process, marked by weak coordination among stakeholders and insufficient commitment to sustained legal reform. As a result, the current system has yet to ensure legal certainty, justice, and accessibility for all citizens. The study argues that ideal regulatory structuring must be rooted in Pancasila and the 1945 Constitution, incorporating the principles of transparency, public participation, justice, legal certainty, and consistency. Furthermore, it emphasizes the need to establish a specialized and independent institution as mandated by Law No. 15 of 2019 to coordinate and manage regulatory formulation effectively. Strengthening this institutional capacity is essential to achieving a legal system that supports social justice and the broader welfare of the Indonesian people.